Dual-Band RFID Antenna for 0.92 GHz Near-Field and 2.45 GHz Far-Field Applications - Zijian Xing; Kun Wei; Ling Wang; Jianying Li (International Journal of Antennas and Propagation)
A novel antenna used in the near field of a 0.92 GHz and the far field of a 2.45 GHz RFID reader system is investigated. The new antenna achieves strong magnetic field distribution over 0.92 GHz with good performance of detecting tags when applied in FCC RFID systems, as well as a good performance of circular polarization at 2.45 GHz. Furthermore, the investigation shows the operation principle by circuit models and the advantages of the structure in terms of the operation frequency and field performances. The advantages of these two bands could be achieved by this novel RFID reader antenna.